2022
DOI: 10.3390/jcm11154266
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Mean and Variance of the Numbers of Medical Visits for Allergic Diseases before and during the COVID-19 Pandemic in Korea

Abstract: The implementation of precautionary measures, such as wearing a mask and social distancing, may have affected allergic diseases during the coronavirus disease 2019 (COVID-19) pandemic. This study aimed to compare the numbers of medical visits for allergic diseases before and during the COVID-19 pandemic. Data were obtained from the Korean National Health Insurance claims database. Monthly numbers of patients for four allergic diseases, i.e., allergic rhinitis (AR), asthma, atopic dermatitis (AD), and allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Additionally, the study period coincided with the COVID-19 pandemic, potentially biasing our results. However, the present study included patients both before (until 29 February 2020) and during COVID-19 (from 1 March 2020) [ 30 ], with the prevalence of CRS being 21.2% (181/853) before COVID-19 and 15.8% (148/936) during COVID-19, so the impact is expected to be minimal. Potential sources of bias in the evaluation of CRS include interobserver variability (minimized by employing two independent otolaryngology specialists) and the tendency of MRI grading to overestimate mucosal thickening and sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study period coincided with the COVID-19 pandemic, potentially biasing our results. However, the present study included patients both before (until 29 February 2020) and during COVID-19 (from 1 March 2020) [ 30 ], with the prevalence of CRS being 21.2% (181/853) before COVID-19 and 15.8% (148/936) during COVID-19, so the impact is expected to be minimal. Potential sources of bias in the evaluation of CRS include interobserver variability (minimized by employing two independent otolaryngology specialists) and the tendency of MRI grading to overestimate mucosal thickening and sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for decreased rates of asthma prevalence could be attributed to fewer hospital visits in Korea regarding asthma overall. [29] The most common explanation for this decrease is that individuals feared contracting COVID-19, which led to less healthcare seeking behavior. However, it has been shown in European countries that this is unlikely since mortality from asthma did not increase, which would have been expected if patients avoided care due to fear.…”
Section: Global Epidemiology and Mechanismmentioning
confidence: 99%
“…Previous studies have shown that during the COVID-19 global pandemic, there has been a decrease in allergic rhinitis symptoms among patients 2,6,[17][18][19][20][21][22][23][24][25][26][27][28][29] This can be attributed to two possible reasons: first, the reduced exposure to allergens because of the COVID-19 lockdown and avoidance of crowded places. Second, the use of face masks as per COVID-19 safety guidelines.…”
Section: Symptoms Of Allergic Rhinitis Domainmentioning
confidence: 99%